Analisis Persepsi Harga, Cita Rasa, Kualitas Layanan dan Fasilitas terhadap Keputusan Pembelian Ulang Mie Gacoan Tegal: Studi Kasus pada Mahasiswa UMUS - Listantia Valentine; Mey Nur Aisyah; Slamet Bambang Riono; Andi Yulianto; Mohamad Badrun Zaman (BADAN PENERBIT STIEPARI PRESS, 2023)
This research aims to analyze the influence of price perception, taste, service quality, and facilities on the decision to repurchase Mie Gacoan Tegal. The population in this study is Mie Gacoan customers in Tegal City. The sample used in this study was 145 people. Data collection was carried out by distributing questionnaires to Mie Gacoan customers. The analysis used in this study is respondent demographics, validity tests, reliability tests, and classical assumption tests. Analysis technique with multiple regression test. The results showed that price perception variables and service quality had a positive and significant effect on repurchase decisions, whereas, for taste and facility variables had a negative and insignificant effect on repurchase decisions. Simultaneously, the perception of price, taste, service quality, and facilities influences the decision to repurchase Mie Gacoan Tegal